Serum exosomal miR‐378 upregulation is associated with poor prognosis in non–small‐cell lung cancer patients - Zhang, Yan (J Clin Lab Anal, 2020)
BACKGROUND: Deregulated circulating microRNAs (miRNAs) are potential biomarkers for the early detection and prognosis prediction of non–small‐cell lung cancer (NSCLC). The aim of the present study was to investigate the expression pattern of serum exosomal miR‐378 in NSCLC and its correlation with clinical variables. METHODS: Quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) was performed to detect serum exosomal miR‐378 levels in 103 patients with NSCLC and 60 control subjects. RESULTS: Our results showed that serum exosomal miR‐378 was significantly overexpressed in NSCLC patients, and serum exosomal miR‐378 upregulation was clearly associated with positive lymph node metastasis and advanced TNM stage. In addition, receiver operating characteristic (ROC) analysis demonstrated that combination of serum exosomal miR‐378 expression and carcinoembryonic antigen (CEA) had a high discriminating power to differentiate NSCLC subjects from controls. Moreover, serum exosomal miR‐378 levels in 73 NSCLC cases were significantly decreased after radiotherapy and could be used as an indicator of radiotherapeutic response in NSCLC. Furthermore, survival analyses revealed that patients with higher serum exosomal miR‐378 expression had poor overall survival. Multivariate analysis showed that serum exosomal miR‐378 expression was independently associated with overall survival. CONCLUSIONS: Collectively, serum exosomal miR‐378 has strong potential as a promising non‐invasive biomarker for screening and monitoring NSCLC.